Bilateral Ischemic Optic Neuropathy Developed under Interferon Therapy. (18th October 2012) - Selcukbiricik, Fatih; Tural, Deniz; Senel, Tuba Elif; Sarıca, Ahmet; Soyluk, Ozlem; Serdengecti, Suheyla
Abstract : Introduction . Interferon is a glycoprotein produced by assigned cells of immune system. It has been used in many different diseases. Although flu-like syndrome, myalgia, rash, hypotension, thrombocytopenia and peripheral neuropathy due to interferon use are encountered frequently, ocular side effects are rare, generally mild and transient. Case Report . 47-year-old female patient, presented with a mass lesion in right renal pelvis. Right radical nephrectomy was applied and the histopathological examination was consistent with papillary renal cell carcinoma. Interferon alpha treatment was started subcutaneously at the dose of 5 MIU/3 times in a week. Four weeks after the interferon therapy, suddenly bilateral visual loss developed. We discussed the diagnosis, followup, and treatment of the patient who developed irreversible ischemic optic neuropathy and had no previous known primary systemic disease to cause this condition. Conclusion . We suggest that patients should be screened for risk factors causing optic ischemic neuropathy, before interferon therapy. Although there was no adequate information in the literature for the followup, patients should be monitorized before, 1 month after, and 2 months after the treatment. And if there is no complication, we suggest that they should be followed up at 3-month intervals.